Cytotoxicity of denture base resins: Effect of water bath and microwave postpolymerization heat treatments - Jorge, Janaina Habib [UNESP]; Giampaolo, Eunice Teresinha [UNESP]; Vergani, Carlos Eduardo [UNESP]; Machado, Ana Lucia [UNESP]; Pavarina, Ana Claudia [UNESP]; Carlos, Iracilda Zeppone [UNESP] (My University, 2004)
Purpose: This study compared the effect of two postpolymerization heat treatments on the cytotoxicity of three denture base resins on L929 cells using 3H-thymidine incorporation and MTT assays. Materials and Methods: Sample disks of Lucitone 550, QC 20, and Acron MC resins were fabricated under aseptic conditions and stored in distilled water at 37°C for 48 hours. Specimens were then divided into three groups: (1) heat treated in microwave oven for 3 minutes at 500 W; (2) heat treated in water bath at 55°C for 60 minutes; and (3) no heat treatment. Eluates were prepared by placing three disks into a sterile glass vial with 9 mL of Eagle's medium and incubating at 37°C for 24 hours. The cytotoxic effect from the eluates was evaluated using the 3H-thymidine incorporation and MTT assays, which reflect DNA synthesis levels and cell metabolism, respectively. Results: The components leached from the resins were cytotoxic to L929 cells when 3H- thymidine incorporation assay was employed. In contrast, eluates from all resins revealed noncytotoxic effects as measured by MTT assay. For both MTT assay and 3H-thymidine incorporation, the heat treatments did not decrease the cytotoxicity of the materials tested. Conclusion: Resins were graded by 3H-thymidine incorporation assay as slightly cytotoxic and by MTT assay as noncytotoxic. Cytotoxicity of the denture base materials was not influenced by microwave or water bath heat treatment.
Keywords: resin; thymidine; animal cell; cell metabolism; controlled study; culture medium; cytotoxicity; denture; DNA synthesis; heat treatment; intermethod comparison; microwave radiation; mouse; nonhuman; polymerization; storage; temperature dependence; Acrylic Resins; Analysis of Variance; Animals; Coloring Agents; Denture Bases; Heat; L Cells (Cell Line); Mice; Mice, Inbred C3H; Microwaves; Molecular Structure; Phase Transition; Tetrazolium Salts; Tritium; Water